História, Teologia e Prática do Centro Ecumênico de Evangelização, Capacitação e Assessoria: uma contribuição para o movimento ecumênico no Brasil - Stoffel, José Carlos (2006)
The present dissertation is a research about History, Theology and Practice of an ecumenical organism The Ecumenical Center of Evangelization, Formation and Consultancy CECA. It was created as a Roman-Catholic entity and has been growing to become ecumenical because of many, namely ecclesiastic reasons. In this essay, I shall analyze the contribution of CECA toward the proliferation of Liberation Theology in Brazil and its practices based on this theological reference, as well as the interrelatedness between the history of this organization with the development of Liberation Theology in Latin America. Simultaneously, a new ecumenical proposal was being elaborated by CECA which has given significant support to the Ecumenical Movement in Brazil. From the thirty years of its history, many things are to been remembered: persons, practices and a proposal of evangelization engaged with structural transformations of society, as historic mediations of the kingdom of God with Christian unity as its main principle toward a new oikoumene, according to God s purpose, announced by biblical prophets and embodied in Jesus Christ.